A review of studies using graphenes in energy conversion, energy storage and heat transfer development. (15th March 2019) - Zhao, Xiaohuan; E, Jiaqiang; Wu, Gang; Deng, Yuanwang; Han, Dandan; Zhang, Bin; Zhang, Zhiqing
Highlights: Graphene used in energy conversion and heat transfer are classified and compared. Performances of energy equipment made of graphene products are investigated. Further application of graphene products in the field of energy is summarized. Heat transfer applications of nano-graphene and graphene coatings are discussed. Abstract: Along with the chic fad energy industry field, the graphene application in energy conversion and management does bring about some benefits in terms of the energy transfer and storage development, the achievement it exerts on the multifaceted innovate approaches. Both current and previous studies on energy conversion, energy storage and energy transfer development, many research results are sufficient to show that all graphene products including graphene paper, film, foam and fiber have a significant role in improving performance. In the energy conversion research on the graphene paper, it has been recently demonstrated that putting the graphene into triboelectric nanogenerators practice possesses higher output performance than traditional generator, which has a maximum strain as large as 200% without evident degradation of the electrical properties. In terms of energy transfer, the graphene fiber application on the battery can significantly increase the charge and discharge rates with enhanced storage capacity of 763 F g −1 . On the energy storage research, the graphene foam can enhance a high density of solar thermal storage up to 269.8 kJ kg −1 for long-term. Nano-graphene and graphene coating provide feasibility for the miniaturization of energy storage equipment which inspired the possibility for portable and foldable devices. The work done in this paper can effectively help promote the application of graphene in energy field. Based on our work, the researchers can choose graphene products (graphene paper, graphene film, graphene foam or graphene fiber) efficiently according to the research object in the future.